Pulmonary Arterial Hypertension: Iron Matters - Ramakrishnan, Latha; Pedersen, Sofia L.; Toe, Quezia K.; Quinlan, Gregory J.; Wort, Stephen J. (Frontiers in Physiology, 2018)
The interplay between iron and oxygen is longstanding and central to all aerobic life. Tight regulation of these interactions including homeostatic regulation of iron utilization ensures safe usage of this limited resource. However, when control is lost adverse events can ensue, which are known to contribute to an array of disease processes. Recently, associations between disrupted iron homeostasis and pulmonary artery hypertension (PAH) have been described with the suggestion that there is a contributory link with disease. This review provides a background for iron regulation in humans, describes PAH classifications, and discusses emerging literature, which suggests a role for disrupted iron homeostatic control in various sub-types of PAH, including a role for decompartmentalization of hemoglobin. Finally, the potential for therapeutic options to restore iron homeostatic balance in PAH are discussed.